Hubungan Komponen Destinasi Wisata dengan Tourist Attitude di Nepal Van Java, Magelang - Prasetyo, Mila Yuliana (Gadjah Mada Journal of Tourism Studies, 2024)
This study examined the relationship between visitor attitudes toward the destination in Nepal Van Java and the components of the tourism destination, such as attractions, accessibility, amenities, activities, and ancillary services. Quantitative research was implemented in conjunction with deductive reasoning. A total of 100 respondents served as samples. Additionally, the technical data analysis employed a correlation test performed with the assistance of SPSS software. The results of this study indicated that there was a correlation between visitor attitudes toward destinations and the components of tourism destinations. The tourism destination's most significant component was attraction, followed by activities, ancillary services, amenities, and accessibility. Despite the accessibility identification of "difficult," Nepal Van Java's attractiveness and the activities it provides for tourists continue to captivate them.